1977
DOI: 10.1073/pnas.74.12.5222
|View full text |Cite
|
Sign up to set email alerts
|

Light-regulated permeability of rhodopsin:egg phosphatidylcholine recombinant membranes.

Abstract: Purified rhodopsin was incorporated into phospholipid bilayers of egg phosphatidylcholine to give recombinant membrane vesicles, which were examined by proton and phosphorus nuclear magnetic resonance spectroscopy. Increased rhodopsin content in the membranes appears to progressively inhibit the molecular motions of the methyl, methylene, and phosphate groups of the phospholipid molecules. This indicates that regions of the rhodopsin molecule interact in a manner that affects the phospholipids from the aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 43 publications
(50 reference statements)
2
13
0
Order By: Relevance
“…Flash illumination, which bleached approximately 80 % of rhodopsin, released all the trapped 45 Ca+; (Hubbell et al 1977). These results were confirmed with NMR techniques where a light-induced permeability increase to Mn 2+ , Eu 2+ and Co 2+ was observed (O'Brien et al 19776). Therefore light induces the formation of a poorly selective permeability pathway in rhodopsin-phospholipid vesicles.…”
Section: (Ii) Vesiclessupporting
confidence: 68%
“…Flash illumination, which bleached approximately 80 % of rhodopsin, released all the trapped 45 Ca+; (Hubbell et al 1977). These results were confirmed with NMR techniques where a light-induced permeability increase to Mn 2+ , Eu 2+ and Co 2+ was observed (O'Brien et al 19776). Therefore light induces the formation of a poorly selective permeability pathway in rhodopsin-phospholipid vesicles.…”
Section: (Ii) Vesiclessupporting
confidence: 68%
“…As to the light-induced rise of Ca 2+ permeability of a rhodopsin-containing membrane, it is apparently very rapid. In our experiments on photoreceptor discs incorporated into a collodion film [2], we not only confirmed observations on the light-dependent increase in disc membrane permeability [24,[42][43][44][45][46][47][48][49][50] but also revealed that such an effect requires < 50 ms. (A faster measurement is impossible because of a conductivity increase due to operation of rhodopsin as a photogenerator of much lower internal resistance than that of the disc membrane. )…”
Section: The 'Dualistic' Schemesupporting
confidence: 88%
“…It has long been proposed that the primary role of rhodopsin is to release an ionic transmitter (Ca"+) from disk membranes (1,2), presumably by acting as a lightactivated Ca"+ channel, and there is now strong evidence for both the release of Ca"+ from disk membranes and its transmitter role in vertebrate outer segments (3)(4)(5)(6). Moreover, purified rhodopsin has been shown to mediate changes in ion permeability for Ca"+ and H+ as well as other cations in recombinant phospholipid vesicles i-n response to light (7)(8)(9)(10) and Ca++ can be released from preloaded disk membrane vesicles (11) by photoexciting rhodopsin. If rhodopsin functions as a light-activated ion channel,' a fundamental question is whether a rhodopsin 'The possibility of a carrier mechanism cannot be ruled out, although the transmembrane structure of rhodopsin does not require it.…”
Section: Introductionmentioning
confidence: 99%